Seahorse nanos3 plays essential roles in germ cell development in the absence of nanos2 - Lingzhen Chen; Lu Tang; Qiang Lin; Yanhong Zhang (Water Biology and Security)
Seahorses are specialized teleosts due to their unique male pregnancy and reproductive physiology. In particular, they have distinct gonad structures and different patterns of gametogenesis development in both sexes. However, the molecular mechanism of germ cell development in seahorses remains unknown. Nanos, which encodes conserved zinc-finger RNA-binding proteins, play essential roles for germline development in both vertebrates and invertebrates. In this study, we characterized the nanos gene family members and their potential roles in germline development in the lined seahorse, Hippocampus erectus. We showed that the nanos family members in the seahorse are the nanos1a, nanos1b, and nanos3 genes, while nanos2, a key germline stem cell (GSC) maintenance factor, is intriguingly absent. More interestingly, nanos3, which is reported to be a female-specific gene, was also highly expressed in male gonads, as well as in the early developmental stages of testes and ovaries. Our results also showed that nanos3 was highly expressed in early meiotic germ cells, and that expression levels of nanos3 were lower in the gonad after TBT exposure. These findings suggest that nanos3 may function during male germ cell development, and in female initial germ cell production – processes which are regulated by nanos2 in other teleosts. This is the first research into how nanos governs germ cell development in an ovoviviparous fish. Our study provides insights into the regulatory mechanisms of germ cells development, as well as the early events during gametogenesis in the family Syngnathidae.